Comparative analysis of phytochemical constituents in different parts of Aspilia africana: A potential medicinal plant for therapeutic applications - Gerheart Winfred Ashong; Edward Ebow Kwaansa - Ansah; Mohammed Alhassan; Prince Nana Adofo; Jeremiah Adu Sarkodie; Boansi Adu Ababio (Elsevier, 2024)
Background: Among the diverse array of plants used in traditional medicine, Aspilia africana is highly valued due to its high efficacy against many ailments and its well-noted potential for wound healing. The plant has been widely used to cure illnesses in traditional medicine, which is practiced throughout much of Africa, where an estimated about 80 % of the population gets their main healthcare from this source. Purpose: This study aimed to qualitatively screen the phytochemical constituents of Aspilia africana to confirm its therapeutic properties and generate scientific proof that justifies its usage in traditional medicine. Study design: Aspilia africana stem, roots, and leaves were screened qualitatively for phytochemical components using pet-ether extracts and distilled water, and qualitative data was generated. Method: Extraction of phytochemicals was done by using the cold maceration method, 150 g of each of the dried parts were taken and packed into 3 separate glass jars containing 500 ml of each solvent (distilled water and pet-ether solvents) and allowed to stand for 24 h. Results: This study found 15 phytochemicals which include tannins, phlobatannins, alkaloids, terpenoids, flavonols, glycosides, phenols, steroids, anthraquinones, saponins, phytosterols, proteins and amino acids, coumarins, cardiac glycosides, and flavonoids in A. africana. The occurrence of the therapeutic components in the aqueous extract of roots, leaves, and stem were nine (9), nine (9), and eight (8) respectively, and that of the pet-ether extract were nine (9), eight (8), and seven (7) in roots, leaves, and stem respectively. Conclusion: The presence of these phytochemicals indicates prospective uses in the pharmaceutical and nutraceutical industries, as well as supports the use of Aspilia africana in traditional medicine. To completely understand and make use of the plant's medicinal qualities, further investigations are required on its anti-microbial activities.